The Impact of the Data Archiving File Format on Scientific Computing and Performance of Image Processing Algorithms in MATLAB Using Large HDF5 and XML Multimodal and Hyperspectral Data Sets - Bennett, Kelly; Robertson, James (IntechOpen, 2011)
None